Relationship of Pectoralis Muscle Area and Skeletal Muscle Strength with Exercise Tolerance and Dyspnea in Interstitial Lung Disease - Merola, Pietro Krauspenhar; Gass, Ricardo; Dorneles, Rui Gustavo Paulus Nene; Gazzana, Marcelo Basso; Gazzoni, Fernando Ferreira; Hochhegger, Bruno; Vergès, Samuel; Berton, Danilo Cortozi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Pectoralis muscle area (PMA) is an easily derived computed tomography-based assessment that can provide insight into clinical features of other skeletal muscles. Respiratory and locomotor muscle dysfunction has been increasingly recognized in patients with interstitial lung disease (ILD). Its contribution to exercise performance has been controversial. Objective: We aimed to investigate if PMA is related with respiratory and locomotor skeletal muscle strength in ILD patients, and if skeletal muscle function is compromised and independently related with exercise capacity and dyspnea. Methods: Cross-sectional study where subjects performed incremental cycling cardiopulmonary exercise testing with maximal inspiratory (MIP) and expiratory (MEP) pressure measurements, and quadriceps maximal voluntary contraction (MVC) before and after exercise. Results: Thirty ILD patients (forced vital capacity [FVC] and lung diffusing capacity [DLCO] of 60±15% and 38±10% of predicted, respectively) and 15 healthy control subjects were studied. Patients presented significantly lower MIP and qMVC compared to controls. PMA was significantly associated with qMVC only (r=0.506; p